Open-Label, Single-Dose, Parallel-Group Study in Healthy Volunteers To Determine the Drug-Drug Interaction Potential between KAE609 (Cipargamin) and Piperaquine - Stein, Daniel S.; Jain, Jay Prakash; Kangas, Michael; Lefèvre, Gilbert; Machineni, Surendra; Griffin, Paul; Lickliter, Jason (Antimicrobial agents and chemotherapy, 2015)
KAE609 represents a new class of potent, fast-acting, schizonticidal antimalarials. This study investigated the safety and pharmacokinetics of KAE609 in combination with the long-acting antimalarial piperaquine (PPQ) in healthy volunteers. A two-way pharmacokinetic interaction was hypothesized for KAE609 and PPQ, as both drugs are CYP3A4 substrates and inhibitors. The potential for both agents to affect the QT interval was also assessed. This was an open-label, parallel-group, single-dose study with healthy volunteers. Subjects were randomized to four parallel dosing arms with five cohorts (2:2:2:2:1), receiving 75 mg KAE609 plus 320 mg PPQ, 25 mg KAE609 plus 1,280 mg PPQ, 25 mg KAE609 alone, 320 mg PPQ alone, or 1,280 mg PPQ alone. Triplicate electrocardiograms were performed over the first 24 h after dosing, with single electrocardiograms at other time points. Routine safety (up to 89 days) and pharmacokinetic (up to 61 days) assessments were performed. Of the 110 subjects recruited, 99 completed the study. Coadministration of PPQ had no overall effect on exposure to KAE609, although 1,280 mg PPQ decreased the KAE609 maximum concentration ( C max ) by 17%. The group that received 25 mg KAE609 plus 1,280 mg PPQ showed a 32% increase in the PPQ area under the concentration-time curve from 0 to infinity (AUC inf ), while the group that received 75 mg KAE609 plus 320 mg PPQ showed a 14% reduction. Mean changes from baseline in the QT interval corrected by Fridericia's method (QTcF) and the QT interval corrected by Bazett's method (QTcB) with PPQ were consistent with its known effects. PPQ but not KAE609 exposure correlated with corrected QT interval (QTc) increases, and KAE609 did not affect the PPQ exposure-QTc relationship. The QTcF effect for PPQ (least-squares estimate of the difference in mean maximal changes from baseline of 7.47 ms [90% confidence interval, 3.55 to 11.4 ms]) was consistent with the criteria for a positive thorough QT study. No subject had QTcF or QTcB values of >500 ms. Both drugs given alone or in combination were well tolerated, with no deaths, serious adverse events (AEs), or severe AEs reported. Most AEs were mild; upper respiratory tract infections, headache, diarrhea, and oropharyngeal pain were most common. PPQ and KAE609 coadministration had no relevant effect on exposure to either agent, and KAE609 did not affect or potentiate the known effects of PPQ on cardiac conduction.